Gerenciamento de resíduos sólidos urbanos: o programa de coleta de lixo da região metropolitana de Goiânia - GO - Nascimento, Alair Ambrosio do (2015)
The purpose of this dissertation was to investigate the program of selective collection of recyclable materials in Goiânia. The survey also proposed raising if the municipality has a Municipal Program of Integrated Solid Waste Management (PMGIRS). This work investigated the performance of recycling cooperatives of recyclable materials in the following aspects: physical structure of cooperatives, working conditions of the members, the formation of cooperatives in networks, partnerships with municipal government, the documentary and legal aspects, and working conditions of members. The interviews were done with the members of the Goiânia City Hall, so as with representatives of the Municipal Environment Agency (AMMA), Goiania Urbanization Company (COMURG), Members of the Social Incubator recyclable materials from the Goiás Federal University (UFG) and representatives of fourteen recycling cooperatives registered by the city of Goiânia.